الفكر التربوي عند الشيخ عثمان دان فوديو: THE EDUCATIONAL THOUGHT OF SHAYKH ’UTHMAN DAN FODIO - Bamba, Adama (Journal of Islamic Educational Research, 2016)
This article aims at identifying the educational thought of Shaykh ’Uthman Dan Fodio, the founder of the Sokoto Caliphate in actual Northern Nigeria. To achieve this objective, this article has adopted a descriptive analytic method in reading his books. This is combined with the historical method in order to set Shaykh Dan Fodio’s personality shaping in its historical context. Accordingly, this article has found that Shaykh Dan Fodio was above his time in though and practice in terms of progressive educational approaches that he provided, such as stressing on the individual and public rights of education, connecting education and learning to the social needs, emphasizing on women education in all fields, etc. Further studies are expected to go beyond the scope of this article to adopt a deep reading on the complete books of Shaykh Dan Fodio and provide a comprehensive view about his educational thoughts and practices.